Nut in Swiss Albino Mice Independently Assessed by the Forced Swim Test - Novianty, Riryn; Yuharmen, Yuharmen; Sofyanti, Nery; Ya’la, Fitra Audhi (LPPM Universitas Muhammadiyah Riau, 2025)
Depression is a global mental health issue and herbal antidepressants are increasingly sought due to the side effects of synthetic drugs. The present study aimed to evaluate the potential of ethyl acetate extract of old areca nut in treating depression of mice subjected to acute and sub-chronic Forced Swim Test (FST). Ethyl acetate extract was injected intraperitoneally 1 h before the FST at a dose of 50 and 100 mg/kg. The 100 mg/kg dose showed the greatest reduction in immobility time (22.29%) during acute testing. Following seven days of treatment, it was discovered that the extract significantly alleviated the immobility time in sub-chronic FST. The results of the phytochemical analysis showed that phenolics present in the ethyl acetate extract are probably active constituents with antidepressant properties. After prolonged administration, the substance has no toxic effects on the bodies of test animals.